2023
DOI: 10.1002/adfm.202308356
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Growth of 2D V3S5 Single Crystal by Chemical Vapor Deposition

Ping Wang,
Qi Feng,
Weikang Dong
et al.

Abstract: Abstract2D intercalated vanadium chalcogenides have attracted intensive interest based on their physical properties and potential applications. However, controllable synthesis of the intercalated vanadium chalcogenides via chemical vapor deposition is still a big challenge. Here, a binary metal precursor co‐reaction growth mechanism to manipulate the evaporation rate of vanadium precursors is reported, thus the intercalated 2D V1+XS2 – V3S5 single crystal can be controllably synthesized. The quality of 2D V3S5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…As depicted in Figure S5a−d, the thickness of ic-2D Ta 1+x S 2 flakes varied from 1.8 to 57.5 nm. 13,41,44 On the other hand, our analysis revealed that ic-2D TaS 2 flakes transform from irregular triangles to curved or truncated triangles and even hexagons. The thickness ranges from 2.7 to 36.0 nm, which was tuned by the modulation of hydrogen concentration (Figure S4h−k and Figure S5e−h).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…As depicted in Figure S5a−d, the thickness of ic-2D Ta 1+x S 2 flakes varied from 1.8 to 57.5 nm. 13,41,44 On the other hand, our analysis revealed that ic-2D TaS 2 flakes transform from irregular triangles to curved or truncated triangles and even hexagons. The thickness ranges from 2.7 to 36.0 nm, which was tuned by the modulation of hydrogen concentration (Figure S4h−k and Figure S5e−h).…”
Section: Resultsmentioning
confidence: 75%
“…Notably, upon the intercalation of Ta atoms into the vdW gaps whether ordered or disordered, the centrosymmetry of T-TaS 2 is prone to be broken, due to a transformation to non-centrosymmetry or the absence of longrange periodicity (Figure S13b and c). 44 Consequently, the assynthesized ic-2D T-Ta 1+x S 2 , featuring disordered intercalated Ta atoms, is expected to exhibit a significant SHG response via disordered intercalation, attributed to the broken inversion symmetry of pure T-TaS 2 (Figure S13d).…”
Section: Resultsmentioning
confidence: 99%
“…At low reaction temperature of Se and low Ar flow rate, the partial vapor pressure of Se and metallic precursors can be modulated for preparing stoichiometric CuCrSe 2 . [38,39] We used atomic force microscopy (AFM) to check the thickness of CuCrSe 2 nanosheet. Figure 1e shows the ultrathin CuCrSe 2 with the thickness of 2 nm, which can be considered as a one-unit cell (1 u.c.)…”
Section: Resultsmentioning
confidence: 99%
“…Vanadium sulfide encompasses several phases, notably including VS 2 , VS 4 , V 2 S 5 , V 2 S 3 , VS, V 3 S 4 , V 3 S 5 , and V 5 S 8 . [ 21,37–42 ] Among these, owing to their exceptionally high theoretical specific capacity, VS 2 and VS 4 have gained significant prominence as anode materials in SIBs and PIBs. The crystal structure of VS 2 is characterized by layering with a layer spacing of 5.76 Å.…”
Section: Scientific Significance Of Vanadium Sulfidesmentioning
confidence: 99%
“…It's important to note that the oxidation state of vanadium remains constant in both VS 2 and VS 4 , while the oxidation state of the sulfide differs, with VS 2 containing S 2 ⁻ monomers and VS 4 featuring S 2 2 ⁻ dimers. With respect to the NiAs‐type VS x compounds, including V 2 S 3 , V 3 S 4 , V 3 S 5 , and V 5 S 8 , these crystal structures formed by self‐ intercalated of either V or VS. [ 37,38,43–45 ] Moreover, it is significant that compounds in the NiAs‐type VS x structural class frequently exhibit a predominance of polar and covalent bonding as opposed to ionic interactions. This is because internal instability can result from ionic interactions that are affected by cation‐cation repulsion.…”
Section: Scientific Significance Of Vanadium Sulfidesmentioning
confidence: 99%